Autoantibodies to cartilage and type II collagen in relapsing polychondritis and other rheumatic diseases. Issue 5 (October 1981) - Ebringer, R; Rook, G; Swana, G T; Bottazzo, G F; Doniach, D
Abstract : Cartilage antibodies were demonstrated by indirect immunofluorescence (IFL) on human fetal cartilage in 6 out of 9 patients with relapsing polychondritis (RPC), in 4 out of 260 patients with rheumatoid arthritis (RA), and in only 1 out of 1016 patients with other disorders. The antibodies were specific for cartilage and evenly stained the whole cartilage matrix. They were predominantly of IgG class and varied in titres from 1:1 to 1:320. Follow-up studies in the RPC patients indicated that higher titres were present during the early acute phase of the disease. Five of the 6 positive cases had developed the disease within the past 12 months, and the 3 negative cases had had the disease for 3 to 7 years when tested. The RA cases showing positive cartilage IFL had no clinical evidence of RPC. Sequential measurements in 2 of the 4 cases showed that these antibodies became detectable some years after the onset of arthritis. Absorption studies with human type II collagen and purified porcine proteoglycan failed to remove the cartilage IFL. Antibodies to human native type II collagen were measured by an enzyme-linked immunosorbent assay. The highest levels were found in the RA sera which also displayed cartilage IFL, but the 2 tests gave discordant results. RPC sera showed the same antibody levels by this method, as did cartilage-IFL-negative RA sera, though both groups had higher mean levels than health controls. The findings that cartilage antibodies are detected in the majority of cases of RPC and only rarely in other diseases suggests these antibodies may play an important role in the pathogenesis of cartilage destruction in RPC.